Influence of Micronutrients in The Alleviation of Immunotoxicity Induced by Poly Aromatic Hydrocarbons Naphthalene and Anthracene: Pharmaceutical Science-Immunotoxicology - M, Sreepriya; V, Joshi; C, Sudha; B, Muthukumaran (International Journal of Life Science and Pharma Research, 2022)
Diet plays a major role in fine tuning the immune system and to combat against dreadful diseases and infections. Micronutrients form an important part of balanced diet and enable efficient functioning of the immune system. Vitamins, minerals and trace elements comprise the major category of micronutrients. Deficiency of micronutrients could culminate in suppression of both adaptive and innate immunity leading to altered immune homeostasis. Anthracene and naphthalene are two environmental pollutants which are highly toxic, carcinogenic poly cyclic aromatic hydrocarbons that gains entry in to the human system through multiple modes. The aim of the current study is to evaluate the potential of four dietary micronutrients Vitamin A, Vitamin C, Folic acid and Zinc to counteract the immunotoxic effects of naphthalene and anthracene on Murine macrophage cell line RAW 264.7. Several cell based assays like MTT assay, LDH leakage assay, Crystal violet test, DCFDA analysis (for ROS generation) and Rhodamine B assay (for measurement of mitochondrial membrane potential) were taken as end point indicators to support the findings of the study. The results showed that, both naphthalene and anthracene triggered the production of ROS, altered mitochondrial membrane potential, and induced strong immunosuppressive effects. The immunosuppressive effect was found to be more prevalent in anthracene treated cells. Pre-treatment with the micronutrients exhibited considerable protection against naphthalene and anthracene induced changes in the cells primarily through the antioxidant and immunomodulatory effects. The overall protective effects offered against naphthalene and anthracene was found to be superior in the Vitamin A treated cells as compared Vitamin C, Folic acid and Zinc treated cells. Prolonged immunosuppression reduces immune surveillance and hence could activate oncogenic signals leading to carcinogenic conditions. Regular micronutrient supplementation in the diet could help considerably to negate or prevent these deleterious conditions.